THE ROLE OF BANKS AND SECURITIES MARKETS IN THE POST-TRANSITION ECONOMIES OF EASTERN EUROPE - Arsov, Sasho (Faculty of Economics - Skopje, Ss Cyril and Methodius University, 2020)
Economic theory predicts that the development of the financial sector should have a positive impact on the overall economic development. Research has predominantly confirmed this expectation, with the remark that at earlier stages of economic development this impact should be higher, while a disproportionate banking sector has detrimental effect on growth through its impact on attracting highly skilled workforce, increased presence of moral hazard and the associated banking crises. This issue has been studied only occasionally in the case of the former socialist economies of Central and Eastern Europe and the former USSR. This paper represents an attempt to analyze the impact of the banking sector and securities markets development on the economic growth of these countries. A sample of 22 countries is assembled, using data from 1995 to 2018 and a panel regression and a GMM technique are used to derive conclusions on the researched topic. The analysis has shown that the banking sector has played a positive role in the economic growth throughout the analyzed period, while the role of the stock market is not significant. This is in line with the previous studies which have confirmed that the positive role of the securities markets should be expected only at higher levels of economic development. Also, the impact of the overall financial sector is deemed to be positive.
Keywords: Financial development; Banking sector; Financial markets; Post-transition